STUDY OF INTERACTION OF COMPONENTS IN THE H3BO3–KNO3–H2O SYSTEM - Yuldasheva, Madina; Makhkamova, Dilnoza; Turayev, Zokirjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The interaction of boric acid with potassium nitrate, the main component of NPK fertilizers, was studied in 0.01 M dilute solutions using the isomolar sequence method. To determine the possible direction of the reaction in the H3BO3 – KNO3 – H2O system, changes in the properties of pH, density, refractive index, viscosity and crystallization temperature of mixtures of 0.01 M boric acid and potassium nitrate solutions in different ratios were determined. The inflection points of the “composition-pH”, “composition-density”, “composition-viscosity” and refractive index dependences were determined. Regardless of the initial concentration of boric acid, when a small amount of potassium nitrate was added, the composition of the solution changed.